Rex or Imperator? Kalojan’s Royal Title in the Correspondence with Innocent III - Dall’Aglio, Francesco (Studia Ceranea, 2019)
In the correspondence between Innocent III and Kalojan of Bulgaria (1197–1207), the title of the Bulgarian ruler is recorded both as rex and imperator. While the pope consistently employs the title rex, Kalojan refers to himself, in every occasion, with the title imperator. Some scholars have speculated that the use of this title was a deliberate political move: styling himself imperator, Kalojan was claiming a much greater political dignity than that of king of Bulgaria, putting himself on the same level as the emperor of Constantinople. On the other hand, while Innocent’s letters were obviously written in Latin, Kalojan’s letters were originally in Bulgarian, translated in Greek, and finally translated from Greek to Latin. Therefore, the use of the word imperator may be just an attempt at translating the term βασιλεύς, not in the sense of Emperor of the Romans but merely in that of autocrat, a ruler whose power was fully independent from any other external political authority. This recognition was of a fundamental importance for Kalojan, since the rulers of Bulgaria’s neighbouring states, the kingdom of Hungary, the Byzantine empire, and especially the Latin empire of Constantinople, were not willing to recognize his legitimacy as an independent sovereign.